KI-Promoted Oxidative Coupling of Styrenes with Indoles under Metal-Free Conditions: Facile Access to C-3 Dicarbonyl Indoles - Zhou, Bochao; Guo, Shiyu; Fang, Zheng; Yang, Zhao; Liu, Chengkou; He, Wei; Zhu, Ning; Li, Xin; Guo, Kai (Synthesis, 2019)
A new and efficient method for the synthesis of C-3 dicarbonyl indoles via oxidative cross-coupling of styrenes with indoles under metal-free conditions has been developed. Moreover, a broad scope of C-3 dicarbonyl indoles in moderate to good yields were obtained, and a plausible mechanism is proposed based on control and isotope-labeling experiments.
Keywords: styrenes; metal free; dicarbonyl indoles; synthetic methods